Back pain in psoriatic arthritis: defining prevalence, characteristics and performance of inflammatory back pain criteria in psoriatic arthritis. Issue 11 (4th August 2018) - Yap, Kristy S; Ye, Justine Y; Li, Suzanne; Gladman, Dafna D; Chandran, Vinod
Abstract : Objective: We aimed to determine the agreement between rheumatologist-judged inflammatory back pain (IBP) and criteria defining IBP in patients with psoriatic arthritis (PsA) and predictive value of IBP in identifying axial involvement in PsA. Methods: Using prospectively collected data, we investigated the agreement between rheumatologist judgement of IBP and IBP criteria (Calin, Rudwaleit and Assessment of Spondyloarthritis International Society) using the kappa coefficient. We also determined the sensitivity, specificity and likelihood ratios of the presence of back pain, rheumatologist-judged IBP and the three IBP criteria for detecting axial PsA (AxPsA). Finally, we compared the clinical and genetic markers in patients with PsA with axial radiological changes with and without back pain. Results: 171 patients (52% male, mean age 46.6 years) were identified. Ninety-six (56.13%) patients reported chronic back pain. Sixty-five (38.01%) had IBP. 54 (32%) patients had evidence of radiological change in the spine. The agreement between rheumatologist judgement of IBP and IBP criteria was highest for the Calin criteria (0.70). Positive likelihood ratio for the presence of radiological axial involvement was highest for Rudwaleit criteria (2.17). No differences between patients with AxPsA with or without back pain were found, except for higher Bath Ankylosing Spondylitis Disease Activity Index and lower prevalence of human leucocyte antigen-B*38 in those with back pain. Conclusion: Rheumatologist-judged IBP or the criteria for IBP developed for ankylosing spondylitis may not perform well when ascertaining axial involvement in PsA.